2020
DOI: 10.1128/jvi.01604-20
|View full text |Cite
|
Sign up to set email alerts
|

The Golgi Calcium ATPase Pump Plays an Essential Role in Adeno-associated Virus Trafficking and Transduction

Abstract: Adeno-associated viruses (AAVs) are dependoparvoviruses that have proven useful for therapeutic gene transfer; however, our understanding of host factors that influence AAV trafficking and transduction is still evolving. Here, we investigate the role of cellular calcium in the AAV infectious pathway. First, we demonstrate a critical role for the host Golgi-resident ATP-powered calcium pump (secretory pathway calcium ATPase 1; SPCA1) encoded by the ATP2C1 gene in AAV infection. CRISPR-based knockout (KO) of ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…This is not in contradiction to published data, given that only functional tests, specifically luciferase expression assays, were performed. 17 However, our data are more consistent with a model where AAVR plays a similar role in AAV transduction to the Golgi calcium transport pump SPCA1, 28 which has recently been described as an essential host factor for intracellular trafficking. Productive intracellular trafficking would then lead to capsid conformational changes that support efficient transduction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is not in contradiction to published data, given that only functional tests, specifically luciferase expression assays, were performed. 17 However, our data are more consistent with a model where AAVR plays a similar role in AAV transduction to the Golgi calcium transport pump SPCA1, 28 which has recently been described as an essential host factor for intracellular trafficking. Productive intracellular trafficking would then lead to capsid conformational changes that support efficient transduction.…”
Section: Discussionsupporting
confidence: 89%
“…Productive intracellular trafficking would then lead to capsid conformational changes that support efficient transduction. 28 …”
Section: Discussionmentioning
confidence: 99%
“…High among those implicated by gene trap and CRISPR screens is ATP2C1 (Table 2), encoding the SPCA1 calcium pump [4,51]. Knockout of ATP2C1 reduces transduction by multiple AAV serotypes but can be rescued by an intracellular Ca 2+ -chelating agent [74]. The impact might be mostly indirect: low Ca 2+ appears to be needed to trigger exposure of VP1u, but there might be pleiotropic effects [74].…”
Section: Trends In Microbiologymentioning
confidence: 99%
“…While several studies have demonstrated the importance of TLR signaling in vivo for hematopoiesis in response to microbial infection, ex vivo studies highlight the innate TLR functionality present in HSPCs. Ex vivo TLR9 activation by CpG DNA can induce mouse common lymphoid progenitors (CLPs) to differentiate to dendritic cells in response to herpesvirus infection (72). Additionally, TLR2 activation of human CD34+ cells in vitro with Pam 3 CSK 4 pushes cells towards a myeloid-biased lineage, generating CD11c+ monocytes and dendritic cells (71,73,74).…”
Section: How Might the Aav Genome Be Sensed As A Pamp In Hspcs?mentioning
confidence: 99%